Hendiadyoıns in gagauz turkic - Çiftçi, Mehmet (Ahmet BURAN, 2021)
Turkic has a rich vocabulary with its terms, stereotypes, proverbs, idioms, loanwords, reduplications and with all meaningful or functionary narrative units, as well as word types. The reduplications we count in this vocabulary are phrases that add richness, color, variety, agility, mobility, power and poetry to the expression as an element of harmony in the text and expression. As well as the reduplications common to each of the Turkic dialect, there are also unique reduplications of the dialects, arising from the geographical, political and religious differences in the context of the historical process of each dialect. In this study, the reduplications seen in Gagauz Turkic, which is in the Oghuz group of Turkic dialects, were discussed. The reduplications determined by scanning the sources were evaluated in terms of sound characteristics, structures, origins and meanings.

Türkçe, sözcük türlerinin yanı sıra terimleri, kalıplaşmış sözleri, atasözleri, deyimleri, yabancı kökenli sözcükleri ve ikilemeleri ile anlamlı veya görevli tüm anlatım birimleri ile zengin bir sözvarlığına sahiptir. Bu söz varlığı içerisinde saydığımız ikilemeler, metinde ve ifadede bir ahenk unsuru olarak anlatıma zenginlik, renk, çeşitlilik, kıvraklık, hareketlilik, güç ve şiirsellik katan söz öbekleridir. Türk lehçelerinin her birinde ortak olan ikilemelerin yanı sıra, lehçelerin her birinin tarihî süreci bağlamında oluşan coğrafî, siyasî, dinî farklılıklardan kaynaklanan kendine özgü ikilemeleri de vardır. Bu çalışmada, Türk lehçelerinin Oğuz grubunda yer alan Gagavuz Türkçesinde görülen ikilemeler ele alınmıştır. Kaynaklardan taranarak tespit edilen ikilemeler; ses özellikleri, yapıları, kökenleri ve anlamları bakımından değerlendirilmiştir.
GAGAVUZ TÜRKÇESİNDE İKİLEMELER
Keywords: Linguistics; Dilbilim